2017
DOI: 10.1007/978-3-319-61382-6_16
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Power Control and Clustering in Underlay Device to Multi-device Communications

Abstract: Underlay device to device multicast communication brings great benefits to cellular networks in term of energy and spectral efficiency, since a group of users can communicate directly by reusing cellular resources. In this paper, we propose a scheme to maximize network energy efficiency (EE) through transmission power control. In addition, to get a compromise between fairness and the overall EE, we analyse a second scheme with fairness factors to maximize minimum individual EE. The problem is formulated as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Observing Table I, clearly the main objectives are either to maximize the sum-throughput or the system capacity, with just a single work investigating EE for D2MD communications. In our previous work [16], we found that, when the aggregate interference is well controlled, a channel can hold up to a few tens of D2MD groups. In such case, the sum-throughput continuously increases as the number of users grows, whereas both the system and the individual EE decrease significantly.…”
Section: B Contributionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Observing Table I, clearly the main objectives are either to maximize the sum-throughput or the system capacity, with just a single work investigating EE for D2MD communications. In our previous work [16], we found that, when the aggregate interference is well controlled, a channel can hold up to a few tens of D2MD groups. In such case, the sum-throughput continuously increases as the number of users grows, whereas both the system and the individual EE decrease significantly.…”
Section: B Contributionsmentioning
confidence: 91%
“…This is not a problem for the power control algorithm as it is able to find the optimal values. For more details we refer the reader to [16].…”
Section: Stabilitymentioning
confidence: 99%
“…However, whereas KNN permits to form homogeneous (equal sized) groups, DL defines the group area as a disk around the group transmitter, so it allows us to consider groups of different sizes, including unicast transmissions as a special case. Based on previous results [ 39 ], we remark that the clustering technique (i.e., using KNN or DL) usually has little impact on the individual or aggregate behavior [ 39 ]. Therefore, we mostly present our results for only one of the algorithms, with similar conclusions being valid for the other one.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Li et al [26] optimised both CU and D2D powers in uplink but did not reuse the channel among multiple D2D pairs. In [27], an uplink channel is shared among multiple D2D pairs while optimising both CU and D2D powers but did not consider the channel assignment.…”
Section: Related Workmentioning
confidence: 99%